2020
DOI: 10.1002/mds.28077
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Susceptibility Associates With Dopaminergic Deficits and Cognition in Parkinson's Disease

Abstract: The objective of this study was to assess the relationship between nigrostriatal magnetic susceptibility and dopamine transporter abnormality and their associations with behavioral and cognitive impairments in patients with Parkinson's disease (PD). Methods: For this case-control study, we enrolled 41 patients with PD and 20 age-matched healthy controls. All participants underwent global physical and cognitive assessments, 3-Tesla brain magnetic resonance imaging including quantitative susceptibility mapping (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 45 publications
2
33
2
1
Order By: Relevance
“…Therefore, R2* relaxometry analysis reached higher spatial resolution might provide auxiliary imaging biomarkers in neurodegenerative diseases, such as PD, besides diffusion-based metrics. Moreover, the dual analyses of R2* relaxometry in WM and QSM in gray matter on a single dataset acquired from mGRE might allow boosting of the more accurate early evaluation of cognitive decline in patients with PD, because the susceptibility changes in the cortical cortex and basal ganglia in PD-MCI were reported using QSM analysis ( Guan et al, 2017 , Uchida et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, R2* relaxometry analysis reached higher spatial resolution might provide auxiliary imaging biomarkers in neurodegenerative diseases, such as PD, besides diffusion-based metrics. Moreover, the dual analyses of R2* relaxometry in WM and QSM in gray matter on a single dataset acquired from mGRE might allow boosting of the more accurate early evaluation of cognitive decline in patients with PD, because the susceptibility changes in the cortical cortex and basal ganglia in PD-MCI were reported using QSM analysis ( Guan et al, 2017 , Uchida et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ApoE‐cholesterol complex is internalized into neurons mediated by LDL‐C receptors and LDL‐C receptor‐related protein (Garcia‐Sanz et al., 2021; Saedi et al., 2021). The increase in LDL‐C may initiate disturbances in cholesterol homeostasis, which may result in damage to neuronal cell membrane structure and loss of synapse function, and negative feedback from this process and may produce a detrimental vicious cycle (Garcia‐Sanz et al., 2021; Uchida et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson's disease (PD), a chronic, progressive neurodegenerative disorder characterized clinically by irreversible, progressive motor and nonmotor dysfunction, occurs mostly in the elderly (Jankovic, 2008; Uchida et al., 2020; Zarkali et al., 2021). Existing management decisions only temporarily lessen PD symptoms and fail to halt disease progression (Raza et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have shown that the iron elevation is associated with cognitive impairment in PD (Thomas et al, 2020;Uchida et al, 2020) and other neurodegenerative diseases (Lei et al, 2020), however, the short-term memory was not influenced by elevated iron in the study by Joppe et al and the pathological α-synuclein caused cognitive impairment was independent of iron enrichment.…”
mentioning
confidence: 82%